The effects of portfolio moderate-carbohydrate and ketogenic diets on anthropometric indices, metabolic status, and hormonal levels in overweight or obese women with polycystic ovary syndrome: a randomized controlled trial - Maryam Sharifi; Amir Saber; Jalal Moludi; Yahya Salimi; Alireza Jahan-Mihan (Nutrition Journal)
Abstract Background Polycystic Ovary Syndrome (PCOS) is one of the most common hormonal disorders in reproductive-age women caused by hyperinsulinemia. The portfolio Moderate-carbohydrate diet (PMCD) is a plant-based diet with a carbohydrate content of 40% and incorporates five cholesterol-lowering foods. While, the ketogenic diet is a high-fat diet with 70% fat, promoting a ketosis state. To the best of our knowledge, no study compared the therapeutic effects of these two diets in PCOS patients. Thus, this study aimed to compare the impact of PLCD and KD on anthropometric indices, metabolic status, and hormonal levels in overweight or obese women with PCOS. Methods This open-label, randomized clinical trial was conducted on forty-six PCOS women. 21 women in PMCD and 19 in the KD group completed the study. The anthropometric indices including body mass index (BMI) and fat body mass (FBM), metabolic markers (fasting blood glucose (FBG)) and plasma lipid profiles including low-density lipoprotein (LDL), triglycerides, and high-density lipoproteins (HDL) were measured. Reproductive hormones such as luteinizing hormone (LH), dehydroepiandrosterone sulfate (DHEA-s) and free testosterone were assessed at the baseline and after the intervention. Results However, after 8 weeks both diets demonstrated enhancement in anthropometric indices (BMI, FBM, lean body mass), metabolic status (FBG, insulin serum levels), and reproductive hormones such as LH, free testosterone, and DHEA-s. The mean difference in the KD improved more than the PMCD in the field of BMI reduction (MD (SD) 2.73 (0.351) vs. MD (SD) 1.71 (0.775)) and LH (MD 4.13 (1.375) vs.MD 2.46 (1.105)). Nevertheless, the lipid profile including LDL-C and triglycerides improved more in the PMCD compared to the KD (MD 33.95 (7.345) vs. MD 23.34 (14.136)) and (MD 38.20 (10.757) vs. MD 57.62 (21.688)) respectively. There were no significant changes in the Ferriman-Gallwey score within or between the two groups. Conclusion The findings revealed that both diets were effective in improving PCOS manifestations. However, the KD exhibited greater effectiveness in enhancing body measurements, metabolic factors, and reproductive hormone levels compared to the PMCD in obese PCOS women. Furthermore, PMCD could be more beneficial for PCOS women with lipide disorders. Registration number of clinical trial IRCT20200912048693N3, Trial registered 2022–12–14. https://www.irct.ir/trial/67548